As indicações geográficas para cafés no Brasil: uma revisão sistemática - Galego, Anna Paula Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Introdução - A expansão da competitividade provocada pelo avanço do neoliberalismo e abertura do mercado mundial no final do século XX, atreladas à novos valores associados ao consumo, conduziram à produção de cafés diferenciados e distinguíveis do café commodity ou convencional. A Indicação Geográfica é uma dessas iniciativas com o objetivo de agregar maior de valor ao produto e de conferir maior identidade aos produtores e regiões de produção. Objetivo – Identificar os impactos locais das Indicações Geográficas para cafés no Brasil. Métodos – Revisão sistemática da literatura. Resultados - Foram identificados os seguintes fatores como impactos locais das Indicações Geográficas para cafés no Brasil: intensificação das relações entre diferentes agentes e do associativismo, padronização da produção e incorporação técnico-científica e elevação da qualidade. Conclusão - Como consequência, entre as contradições do processo de certificação em função desses fatores identificados, há a substituição de práticas tradicionais por práticas produtivas intensivas e um processo de recommoditização.

Introduction - The expansion of competitiveness caused by the advance of neoliberalism and the opening of the world market at the end of the 20th century, linked to new values associated with consumption, led to the production of differentiated and distinguishable coffees from commodity or conventional coffee. The Geographical Indication is one of these initiatives with the objective of adding more value to the product and giving greater identity to producers and production regions. Objective – To identify the local impacts of the Geographical Indications for coffees in Brazil. Methods – Systematic literature review. Results - The following factors were identified as local impacts of the Geographical Indications for coffees in Brazil: intensification of relations between different agents and associations, standardization of production and technical-scientific incorporation and improvement of quality. Conclusion - As a consequence, among the contradictions of the certification process due to these identified factors, there is a substitution of traditional practices for intensive productive practices and a process of recommoditization.
Geographical indications for coffees in Brazil: a systematic review
Keywords: Indicação geográfica; Café; Recommoditização; Geographical indication; Coffee; Recommoditization